2017
DOI: 10.1186/s12918-017-0509-y
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of gene-gene dynamics influence networks based on a Boolean model

Abstract: BackgroundIdentification of novel gene-gene relations is a crucial issue to understand system-level biological phenomena. To this end, many methods based on a correlation analysis of gene expressions or structural analysis of molecular interaction networks have been proposed. They have a limitation in identifying more complicated gene-gene dynamical relations, though.ResultsTo overcome this limitation, we proposed a measure to quantify a gene-gene dynamical influence (GDI) using a Boolean network model and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 70 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…In other words, the network is more sensitive when the double knockout mutation occurs in the order involving fewer paths than in the reverse order. We note that our previous study showed that the dynamics influence from a gene on another gene is likely to be lessened as the path length increases and the number of paths decreases [50]. Thus, it is interesting that both the 'Longer-path direction' and 'Fewer-paths direction', which showed relatively higher mutation-sensitivity values, represent ways to induce a smaller dynamics-influence from the first mutated gene on the second mutated gene than the reverse order.…”
Section: Relation Between Structural Characteristics and Orderedmutatmentioning
confidence: 75%
See 1 more Smart Citation
“…In other words, the network is more sensitive when the double knockout mutation occurs in the order involving fewer paths than in the reverse order. We note that our previous study showed that the dynamics influence from a gene on another gene is likely to be lessened as the path length increases and the number of paths decreases [50]. Thus, it is interesting that both the 'Longer-path direction' and 'Fewer-paths direction', which showed relatively higher mutation-sensitivity values, represent ways to induce a smaller dynamics-influence from the first mutated gene on the second mutated gene than the reverse order.…”
Section: Relation Between Structural Characteristics and Orderedmutatmentioning
confidence: 75%
“…There have been many previous studies on the relationship between the structural properties and the dynamical behavior in biological networks [45,50,51]. Inspired by them, we investigated the relationships between some structural properties and ordered-mutation-inducing dynamics ( Fig.…”
Section: Relation Between Structural Characteristics and Orderedmutatmentioning
confidence: 99%
“…In this study, the examination of attractors is needed to find the affected genes. The affected genes were obtained based on our previous work about gene–gene dynamics influence networks [ 29 ]. To implement this, we specified a set of initial states, , and computed a state trajectory starting at every until an attractor is found.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it has been used to analyze oncogene rules in Non-small cell lung cancer [ 25 ], to model the C. albicans yeast for hyphal transition [ 26 ], to a matrix cell density sensing to contact inhibition, proliferation, migration, and apoptosis [ 27 ], or to illustrate the regulatory effects in cervical cancer [ 28 ]. A previous study showed that the dynamics influence of a gene to another genes has some interesting structural characteristics in the signaling network [ 29 ]. This study can be extended because the pleiotropy is understood as the difference of the dynamics influence against different mutation types.…”
Section: Introductionmentioning
confidence: 99%
“… Integrated protein-protein interaction network construction using DIP, Biogrid, Reactome and HPRD data; refinement/correction using relationship of functional similarity and proximity scores [ 13 ]. Boolean network modeling; topology comparison of gene-gene dynamics influence and gene-gene molecular interaction networks [ 14 ]. Integration of gene regulatory network inference with constraint-based metabolic models to simulate growth phenotype and exchange fluxes [ 15 ].…”
Section: Manuscript Submission and Reviewmentioning
confidence: 99%